A hypothesis for temporal coding of young and mature granule cells - Rangel, Lara M.; Quinn, Laleh K.; Chiba, Andrea A.; Gage, Fred H.; Aimone, James B. (Frontiers in Neuroscience, 2013)
While it has been hypothesized that adult neurogenesis plays a role in the encoding of temporal information at long time scales, the temporal relationship of immature cells to the highly rhythmic network activity of the hippocampus has been largely unexplored. Here, we present a theory for how the activity of immature adult-born granule cells relates to hippocampal oscillations. Our hypothesis is that theta rhythmic (5-10 Hz) excitatory and inhibitory inputs into the hippocampus could differentially affect young and mature granule cells due to differences in intrinsic physiology and synaptic inhibition between the two cell populations. Consequently, immature cell activity may occur at broader ranges of theta phase than the activity of their mature counterparts. We describe how this differential influence on young and mature granule cells could separate the activity of differently aged neurons in a temporal coding regime. Notably, this process could have considerable implications on how the downstream CA3 region interprets the information conveyed by young and mature granule cells. To begin to investigate the phasic behavior of granule cells, we analyzed in vivo recordings of the rat dentate gyrus, observing that the temporal behavior of granule cells with respect to the theta rhythm is different between rats with normal and impaired levels of neurogenesis. Specifically, in control animals, granule cells exhibit both strong and weak coupling to the phase of the theta rhythm. In contrast, the distribution of phase relationships in neurogenesis-impaired rats is shifted such that they are significantly stronger. These preliminary data support our hypothesis that immature neurons could distinctly affect the temporal dynamics of hippocampal encoding.